2011
DOI: 10.3109/0142159x.2011.577120
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from medical students’ perceptions of learning reflective skills: A multi-institutional study

Abstract: These findings highlight potential ways to revise and improve engagement with the reflective learning components of undergraduate courses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 19 publications
1
65
0
3
Order By: Relevance
“…The studies also show that students recognize writing as an element that helps deepen understanding of those situations which provide the basis for reflection (Vivekananda-Schmidt et al, 2011) and consider reflective diary writing as an aid to better relate theory and practice, clarify the profession, develop coping skills for practical situations and provide a better understanding of new information (Langley and Brown, 2010).…”
Section: Reflective Learning At University Students' Viewsmentioning
confidence: 99%
“…The studies also show that students recognize writing as an element that helps deepen understanding of those situations which provide the basis for reflection (Vivekananda-Schmidt et al, 2011) and consider reflective diary writing as an aid to better relate theory and practice, clarify the profession, develop coping skills for practical situations and provide a better understanding of new information (Langley and Brown, 2010).…”
Section: Reflective Learning At University Students' Viewsmentioning
confidence: 99%
“…Vivekananda-Schmidt et al (2011) reported that students found informal discussions with peers and tutors beneficial, whereas they were more conscious of their reflection in written tasks secondary to tension between the private nature of their thoughts and an inability to know who could read these personal feelings. A 2003 study at the University of Sydney introduced a personal and professional development strand to its first year medical students which involved completing a portfolio and confidential interview with a member of staff (Gordon, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Entre las contribuciones del AR percibidas por los estudiantes destacan: el hecho de que les ayuda a ser más conscientes de lo que aprenden y como aprenden (Turner y Beddoes, 2007); a identificar necesidades de formación (Langley y Brown, 2010); a identificar aspectos positivos y mejorables de sus actitudes ante el aprendizaje y la profesión (Langley y Brown, 2010;Williams y Wessel, 2004). También subrayan las principales dificultades que han experimentado en el desarrollo de experiencias de aprendizaje reflexivo; entre estas, las relacionadas con la falta de habilidades para la narración escrita (Turner y Beddoes, 2007); las dudas sobre el nivel de revelación o apertura personal conveniente (Langley y Brown, 2010;Vivekananda-Schmidt, Marshall, Stark, Mckendree, Sandars, y Smithson, 2011). Suelen además tener la percepción de que hay otras tareas más importantes, como la preparación de proyectos o de exámenes, que requieren mucho más su atención que las tareas relacionadas con el AR (Langley y Brown, 2010).…”
Section: Palabras Claveunclassified
“…Ello coincide con aportaciones de Langley y Brown, (2010), Turner y Beddoes, (2007), Vivekananda-Schmidt, et al, (2011), Williams y Wessel, (2004) que recogen los puntos de vista de los estudiantes que han participado en actividades de narración reflexiva en distintos ámbitos profesionales. Turner y Beddoes (2007) observaron que los estudiantes consideraban que la tarea reflexiva les había ayudado a desarrollar procesos de pensamiento y a ser más conscientes de cómo aprenden y de lo que saben sobre el tema del trabajo.…”
Section: Conclusionesunclassified